الفعالية الاقتصادية والبيئية للمنتوج كأداة لتحقيق التنمية المستدامة في المؤسسة –دراسة الحالة مؤسسة الدهن سوق أهراس- - هدى غريب; لبنى سقني (My University, 2021)
This study aims to highlight the role played by the economic effectiveness of the product in urging those who are related to production ,whether producers or consumers , to integrate the environmental dimension in its broad sense , and this is what made economic institutions adopt a comprehensive quality system that seeks to achieve product quality and product quality at the lowest costs and more quality in its product ,as for the iso 14000 environmental management system , institutions seek to adopt and work with , as it contributes to reducing cost , time and effort during audits and audits, as well as protecting the environment from the negative outputs of the institution and reducing environmental damage caused by the production process. we conducted a field study in the national foundation for painting in souk ahras , where the foundation for painting is taking a set of preventive measures and policies to preserve the environment and reduce damage caused by the production process ,and this is through various measures , and the foundation seeks to adopt the iso14000 environmental management system, and is keen to improve its products and quality in order to continue and survive ln the market. ....................................... تهدف هذه الدراسة إلى إبراز دور الذي تلعبه الفعالية الاقتصادية للمتوج في حث من هم على علاقة بالإنتاج سواء كان منتجين أو مستهلكين بضرورة إدماج البعد البيئي بمفهومه الواسع ، وهذا ما جعل المؤسسات الاقتصادية تبني نظام الجودة الشاملة التي تسعى لتحقيق جودة المتوج و نوعية المتوج بأقل التكاليف و أكثر جودة في منتجاتها ، فبالنسبة لنظام الإدارة البيئية iso14000 تسعى المؤسسات لتبنيها و العمل بها فهي تساهم في تقليل التكلفة والوقت والجهد أثناء عمليات التدقيق و المراجعة و كذلك حماية البيئية من المخرجات السلبية للمؤسسة وتقليل أضرار البيئية الناجمة عن العملية الإنتاجية . قمنا بدراسة ميدانية في مؤسسة الوطنية للدهن بسوق أهراس حيث تقوم مؤسسة الدهن باتخاذ مجموعة من الإجراءات والسياسات الوقائية للحفاظ على البيئة وتقليل الضرر الناجم من العملية الإنتاجية وهذا بتدابير متنوعة، وتسعى المؤسسة إلى تبني نظام الإدارة البيئية iso14000 ،كما تحرص على تحسين منتجاتها وجودتها من أجل الاستمرار والبقاء في السوق.